THE EFFECT OF CUSTOMER EXPERIANCE AND PERCEIVED VALUE ON APARTMENT RESIDENT LOYALTY - Sandra Oktaviana Pinaraswati; Sri Susilowati; Ilya Farida; Ika Devy Pramudiana (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Destination research is to examine the influence of customer experience and perceived value on the loyalty of residents of the Tamansari Prospero Sidoarjo Apartment. The research was designed in the form of a causal relationship between variables. This research uses primary data. The research population was the residents of Tower Fortuna Apartemen Tamansari Prospero Sidoarjo totaling 200 people. While the sample is 133 people with accidental sampling technique and data collection using a questionnaire. The analysis technique uses multiple linear regression analysis. The results of the study are that customer experience and perceived value have a significant effect on the loyalty of apartment residents, customer experience has a significant effect on the loyalty of residents of the Tamansari Prospero Sidoarjo Apartment and perceived value has a significant effect on the loyalty of residents of the Tamansari Prospero Sidoarjo Apartment